2003
DOI: 10.1002/app.13400
|View full text |Cite
|
Sign up to set email alerts
|

Study on the structure and processibility of the iodinated poly(vinyl alcohol). I. Thermal analyses of iodinated poly(vinyl alcohol) films

Abstract: ABSTRACT:To get more information on the structure of iodinated poly(vinyl alcohol) (PVA), thermal analyses of unoriented and oriented PVA films were conducted. Unoriented and oriented PVA films iodinated with aqueous solutions at selected concentrations were carried out by thermogravimetry (TG) and differential scanning calorimetry (DSC). The TG curves for the iodinated film shows four or five weight-loss zones associated with degradation and evaporation of excess I 2 molecules and I 2 molecules from I 5 Ϫ , p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The sharp band at 1089 cm −1 is responsible for the COC stretching of ester group present in the PVA backbone. The corresponding bending and wagging of CH 2 vibrations are observed at 1438 and 1378 cm −1 respectively, and CH wagging at 1247 cm −1 28, 29…”
Section: Resultsmentioning
confidence: 97%
“…The sharp band at 1089 cm −1 is responsible for the COC stretching of ester group present in the PVA backbone. The corresponding bending and wagging of CH 2 vibrations are observed at 1438 and 1378 cm −1 respectively, and CH wagging at 1247 cm −1 28, 29…”
Section: Resultsmentioning
confidence: 97%
“…Shin et al [168][169][170][171] and Woo et al [172] embarked on the study of the structure and processability of iodina tion products of oriented and unoriented PVA using I 2 /KI solution at room temperature for 24 h. The crystallinity of oriented and unoriented PVA subjected to iodination was 21.3% and 37.0%, respectively. The weight gains and molar ratios of the unoriented and oriented films increased rapidly with I 2 /KI concentration to 1.0 mol/l and 0.5 mol/l, respectively.…”
Section: Iodine-proteinic Fiber Complexesmentioning
confidence: 99%
“…This change in crystallinity signifies the structural regularity occurring in the main chains of the polymeric molecules on doping. stretching vibration associated with PVA molecule [12,13]. It is observed that after the action of ZnO nanoparticles dispersing in the PVA matrix the FTIR spectra exhibit several irregular shifts related to corresponding bands with change in intensities of pure PVA as presented in Table 1.…”
Section: Xrd Studies Ofmentioning
confidence: 99%